MALNUTRITION, DEVELOPMENTAL DELAY, AND IMPAIRED SOCIAL MATURITY IN RELATION TO TYPE OF CONGENITAL HEART DISEASE AMONG 0–15-YEARS-OLD CHILDREN - D Shivaashankari; K E Elizabeth; K M Sanjay; K Rugmini; S Kiron (Innovative Journal of Medical and Health Sciences, 2021)
Background: Children with congenital heart disease (CHD) have impaired growth and development with adverse outcome. Objectives To determine nutritional status, developmental, and social quotient among 0-15-year-old children with CHD and the association with type of CHD. Methodology: Among children enrolled under RBSK Scheme, relevant history and examination findings were recorded using a structured proforma. Nutritional status was assessed using anthropometric measurements, Developmental quotient (DQ) using developmental screening test-Bharat Raj and Social quotient (SQ) using Vineland Social Maturity scale-Malin’s Indian adaptation. Results: Out of 60, 46.7% were <5 years old, Male:Female ratio 1:1.4. 86.6% had ACHD, 13.4% CCHD. 61.7% were underweight (ACHD -59.6%, CCHD -75%). 48.3% had stunting (ACHD -44.2%, CCHD -75%); significantly more in CCHD (p <0.01). 66.7% had wasting (ACHD -63.5%, CCHD -87.5%). 48% had thinness/low BMI (ACHD -46.2%, CCHD -62.5%); significantly more in >5-yrs-old group (p<0.01). 63.3% had low DQ <85 (ACHD -59.6%, CCHD -87.5%). 86.7% had low SQ <85 (ACHD -84.6%, CCHD -100%). Mean DQ was low, 74.2 +/-17.9 (ACHD -77.23 +/-17.2, CCHD -57.87 +/-16); significantly more in CCHD (p <0.01). Mean SQ was low 63.18 +/-17.5 (ACHD -65.21 +/-17.2, CCHD -50 +/-12.8); significantly more in CCHD (p <0.01). Conclusion: Malnutrition, developmental delay, and impaired social maturity were common; stunting and lower DQ and SQ significantly more in CCHD and low BMI in >5-yrs.-old category. More females being enrolled indicate less gender bias. As RBSK scheme, addresses birth defects, developmental delay, and nutritional deficiencies and accredits private institutions, it is a big boon to children with CHD. Keywords: Malnutrition, Congenital Heart Disease, Developmental Delay, Impaired Social Maturity, DQ, SQ, Stunting, Underweight, Wasting, RBSK.